Multiple Pregnancy: Epidemiology and Association with Maternal and Perinatal Morbidity - Danielly Scaranello Santana; Fernanda Garanhani Surita; José Guilherme Cecatti (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Twin pregnancy accounts for 2 to 4% of total births, with a prevalence ranging from 0.9 to 2.4% in Brazil. It is associated with worse maternal and perinatal outcomes. Many conditions, such as severe maternal morbidity (SMM) (potentially life-threatening conditions and maternal near-miss) and neonatal near-miss (NNM) still have not been properly investigated in the literature. The difficulty in determining the conditions associated with twin pregnancy probably lies in its relatively low occurrence and the need for larger population studies. The use of the whole population and of databases from large multicenter studies, therefore, may provide unprecedented results. Since it is a rare condition, it ismore easily evaluated using vital statistics from birth e-registries. Therefore, we have performed a literature review to identify the characteristics of twin pregnancy in Brazil and worldwide. Twin pregnancy has consistently been associated with SMM, maternal near-miss (MNM) and perinatal morbidity, with still worse results for the second twin, possibly due to some characteristics of the delivery, including safety and availability of appropriate obstetric care to women at a high risk of perinatal complications.